Implementasi Metode Activity Based Costing dalam penentuan Harga Pokok Jasa dan Analisis Pencatatan serta Pelaporan Keuangan sebagai upaya Optimalisasi Laba - Tria Hasna Lesmana; Neneng Dahtiah (Indonesian Accounting Literacy Journal, 2026)
The rapid growth of the service industry has intensified business competition, requiring companies to accurately determine service costs in order to improve profitability. This study aims to analyze the application of the Activity-Based Costing (ABC) method in determining service costs and to evaluate financial recording and reporting practices as an effort to optimize profits at Teman Tamu. A qualitative approach with a case study design was employed. Data was collected through interviews, observations, and documentation, and analyzed by identifying activities, determining cost drivers, calculating service costs using the ABC method, and evaluating financial recording and reporting practices. The findings indicate that the ABC method provides more accurate service cost calculations than traditional costing by allocating overhead costs based on actual activities. In addition, the company’s financial recording and reporting remain limited to simple cash-based records and have not yet complied with SAK ETAP, reducing the reliability of financial information for managerial decision-making. The study contributes to management accounting theory by extending the application of Activity-Based Costing to the guest service industry and demonstrating the importance of integrating accurate costing with proper financial reporting to support profit optimization. However, this research is limited to a single case study, focuses only on guest service activities, and relies on qualitative evidence, which may limit the generalizability of the findings to other service industries.